Electrocardiogram Showing a High P-wave in a Lung Cancer Patient with Tip Malposition of PICC:A Case Report - Chunli LIU; Liyong XU; Dingbiao JIANG; Ruchun SHI; Jing MAO; Lagen LIU; Chuanyin CHEN; Tao JIN; Aifeng MENG (国际转化医学杂志（英文版）, 2020)
Background: It is recommended that electrocardiogram (EKG) showed a high P wave change, post-operation chest X-ray (CXR) should not be needed to confirm the tip of PICC location. However, in this case, the EKG showed a high P-wave change; a followed CXR revealed the tip malposition in the superior vena cava (SVC).Methods: A power PICC was placed under the ultrasound-guided modified seldinger technique in a 55-year-old man with Lung cancer. Postoperative CXR revealed that the catheter tip was ectopic in the SVC. EKG was used for adjusting the malposition, EKG showed a P-wave elevation. However, a followed CXR revealed that the tip of the catheter was still ectopic in the SVC. We conducted the second adjustment. The amplitude change of P-wave was observed from standard to high-peak and then to a downward deflection on the leading edge of the P-wave. The catheter tip was correct in the lower third of SVC.Results: We successfully adjusted the malposition of PICC with the EKG method.Conclusion: There is a risk that we cannot recognize the PCC tip malposition in the SVC with EKG, we must observe the typical P-wave change from standard to high peak and then to biphasic.